Kontrol Diri Mahasiswa Dengan Kecanduan Internet - Uyun, Muhamad; Ismail, M. Tarmizi; Damayanti, Ester Claudya; Fitriani, Yulia (Badan Penelitian dan Pengembangan Daerah KabupatenMuara Enim, 2022)
Self-control is significant, particularly for internet addicts; without good self-control, the lifeactivities of internet addicts students will be disturbed,especially those related to themselves,academic and non-academic; therefore, a researcher is interested in proving it empirically. Thisstudy aimed to determine the correlation between self-control and internet addiction in collegestudents. The analysistechnique to test the hypothesis is using the product-moment.The hypothesistesting results showed a significant negative correlation between self-control and internet addiction,meaning that the higher the self-control, the lower the internet addiction, and vice versa,the lowerthe self-control, the higher the internet addiction in students with a correlation r-value of-0.507 with(p < 0.01).The practical contribution of self-control to the internet addiction variable is 25.74%,which means that the effect is 25.74% on internet addiction in students.